Ambient light intensity and direction determine relative attractiveness of yellow traps to Rhagoletis indifferens (Diptera: Tephritidae). Issue 6 (17th March 2015) - Yee, W.L.
Abstract: Understanding factors that influence attraction of tephritid fruit flies (Diptera: Tephritidae) to objects can lead to development of more sensitive traps for fly detection. Here, the objective was to determine if differences in attractiveness between two sticky yellow rectangle traps to western cherry fruit fly, Rhagoletis indifferens Curran, depend on ambient light intensity and direction. The translucent plastic Yellow Sticky Strip (YSS) was compared with the less translucent yellow cardboard Alpha Scents (AS). Flies were released inside a box or cage opposite a trap or traps illuminated from outside at different intensities to generate variable light passage. Regardless of type, the trap with greatest light passage was most attractive. When the same light intensity was shone on both traps, the YSS, which allowed greater light passage, was more attractive than the AS. When the light was inside a cage and shone onto the two traps in the same direction as approaching flies, the AS reflected more light and was more attractive. A field experiment generally supported light passage effects seen in the laboratory. Results suggest trap placement with respect to sunlight intensity and direction affects light passage and the attractiveness of yellow traps to R. indifferens .